PENGARUH FRAUD DIAMOND MODEL DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017 - 2019) - Mohamad Zidane Ramadhan; Dul Muid (Diponegoro Journal of Accounting, 2021)
The credibility of the financial statements issued by the company is very important for stakeholders. However, the intense business competition in Indonesia has caused some company management to commit fraudulent actions for private gain. This study examines the points contained in the fraud diamond theory in its effect on fraudulent acts of financial statements committed by managers.The sample data population in this study were all manufacturing companies listed on the IDX in 2017 - 2019. The purposive sampling method was used in this study to determine the sample company data to be tested. Using this method, a sample of 150 companies was obtained using the multiple regression analysis method.The results of this study indicate that the pressure and opportunity variables have a significant positive relationship to the disclosure of financial statement fraud. The independent variable rationality has an insignificant positive relationship with the disclosure of financial statement fraud, while the capability variable has an insignificant negative relationship with the disclosure of financial statement fraud.